Pengobatan Asma Ditinjau Dari Tradisional Chinese Medicine Dan Biologi Molekuler - Arfan Yuslam Sungkar; Tjhia Khie Khiong; Suminah Suminah (STIKes Ibnu Sina Ajibarang, 2023)
Molecular Biology and Chinese Medicine are two very different concepts in understanding disease, one coming from the west and the other from the east. In recent times the idea of combining these two concepts has emerged, resulting in research studies related to combining these two things, for example examining the effects of certain Chinese Medicine herbs from a Molecular Biology point of view. This research uses a descriptive qualitative literature method that describes the relevant theories underlying the topic of asthma treatment in Chinese Medicine and Molecular Biology. The results of this study found that Molecular Biology can explain the mechanism of action of certain herb ingredients in the case of Asthma. So this study concludes that Molecular Biology and Chinese medicine can complement each other in understanding human health and disease. However, further research is needed to understand more deeply how Chinese medicine can affect human biological systems.